The Role of Islamic Banks in Empowering MSMEs Based on Islamic Economics - Mohammad Fahrud Taufiq; M. Miftahur Rizqi; Achmad Budi Susetyo (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector in Indonesia's economy due to their role in employment and economic growth. However, access to financing that aligns with Islamic principles remains a significant challenge. Islamic banks emerge as an alternative solution by offering interest-free financial products and promoting economic empowerment grounded in Islamic values. This study aims to analyze the role of Islamic banks in empowering MSMEs based on Islamic economics, focusing on financing, mentoring, and capacity building. The research employs a qualitative approach through literature reviews and in-depth interviews with MSME actors and Islamic bank representatives. The findings indicate that Islamic banks serve not only as financial providers through instruments such as mudharabah and musyarakah, but also as strategic partners in managerial development, entrepreneurial training, and market access. The concept of maqashid sharia underpins efforts to foster economic blessings and distributive justice for small business actors. In conclusion, the empowerment of MSMEs by Islamic banks demonstrates the synergy between Islamic financial principles and Islamic economic values, contributing to the sustainable strengthening of the ummah's economy.